Corruption and Elections: Abdul Khoir's Political Image-Building Strategies to Gain Votes in Electoral District 5 of Depok City in the 2024 Legislative Election - Sadewa, Ardhanareshwara; Nurdin, Nurdin (ARISTO, 2024)
This study examines Abdul Khoir's political imaging strategy in attracting potential voters during the 2024 election contest. The novelty of this research lies in Abdul Khoir's success in utilizing an imaging strategy to secure a seat in the Regional People's Representative Council (DPRD) despite his background as a former convict and competing in an electoral district with a relatively high average level of education. This study employs a qualitative descriptive method to gain an in-depth understanding of the phenomenon through data collection in a natural setting. The findings conclude that Abdul Khoir managed to build a political image as a problem-solver, caring, and approachable figure, despite facing the stigma of his past as a former convict in a corruption case. His efforts included tangible actions such as improving public facilities and leveraging modern social media platforms like TikTok. Through consistent and relevant personal branding strategies, he stood out as a credible figure, adaptive to societal dynamics, particularly in Electoral District 5 of Depok City, while fostering public trust through authentic and emotional approaches.